2021
DOI: 10.1017/s0950268821002053
|View full text |Cite
|
Sign up to set email alerts
|

The first 8 months of COVID-19 pandemic in three West African countries: leveraging lessons learned from responses to the 2014–2016 Ebola virus disease outbreak

Abstract: Experience gained from responding to major outbreaks may have influenced the early COVID-19 pandemic response in several countries across Africa. We retrospectively assessed whether Guinea, Liberia, and Sierra Leone, the three West African countries at the epicentre of the 2014-2016 Ebola virus disease outbreak, leveraged the lessons learned in responding to COVID-19 following the World Health Organization's declaration of a public health emergency of international concern (PHEIC). We found relatively lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“… 15–17 The Ebola outbreak was declared a public health emergency of international concern as it might result in an unprecedented outbreak, and the lessons learned from the Ebola outbreaks were crucial to developing the COVID-19 responses in Africa. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 15–17 The Ebola outbreak was declared a public health emergency of international concern as it might result in an unprecedented outbreak, and the lessons learned from the Ebola outbreaks were crucial to developing the COVID-19 responses in Africa. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…This finding was consistent with the report from Barrie et al ( 16), the overall weighted seroprevalence was 2.6% in Sierra Leone in March 2021, and overall seroprevalence was low compared with countries in Europe and the America. Similarly, results from a previous report showed that there were relatively lower incidence rates across three countries in Africa (Sierra Leone, Guinea, and Liberia) compared to many parts of the globe (17). In Nigeria, there were 802,143 tests conducted from February 2020 to April 2021, with a resulting positivity rate of 3.2%, and 66,121 and 91,644 people tested positive for SARS-CoV-2 infection during two waves (18).…”
Section: Discussionmentioning
confidence: 57%
“…Also, there were lower numbers of confirmed cases and deaths than in some developed countries, such as the United States, UK, Italy, and Brazil ( https://covid19.who.int/ ). The following factors could contribute to this continent appearing to be more resistant to SARS-CoV-2 than other continents, these factors are a low testing rate, poor documentation of causes of death, a younger population, a lower population density, low income, less travel, a good vitamin D status as a result of exposure to sunlight, cross-immunity from other viruses (including coronaviruses), and lessons learned from other infectious diseases such as HIV and Ebola ( 15 , 16 ). Indeed, most West Africans have basic knowledge of COVID-19 and show a positive attitude toward the disease ( 17 ).…”
Section: Discussionmentioning
confidence: 99%